Analisis Kebutuhan dan Keinginan Konsumen Untuk meningkatkan Pelayanan di Hotel Santika Depok (Jurnal Ilmiah Pariwisata, 2016)
One of the cities on the outskirts of Jakarta, Depok city is also progressing thedevelopment of accommodation and infrastructure in the field of tourism is very rapid. Tourism consists of various aspects one of which is the aspect of accommodation ie hospitality accommodation. With the increasing number of new hotels popping up, this has an impact on increasing competition in the business in the hospitality industry. With increasing competition in the hospitality business, the company is required to improve the quality of service in order to withstand competition in the hospitality business world. This type of research that will be used is descriptive research that describes a particular situation through questions 5W + 1H. Methods of data analysis in this research is quantitative method is by using Cartesian diagram calculations. The results showed that there are two attributes that are considered important in determining customer satisfaction is hotel has complete amenities (shampoo, soap, toothbrushes, etc.). Based on the Customer Satisfaction Index (CSI), in the know that CSI value of77.04%. This illustrates hotel guests santika Depok quite satisfied with the performance of the services provided by the hotel staff and from the analysis of consumer needs